Olopachys (Olopachylaella) gronychi subgen. nov., sp. nov., a new species of mite from Bulgaria (Acari: Mesostigmata: Pachylaelapidae) - Mašán, Peter (Zootaxa, 2007)
A new subgenus and species, Olopachys (Olopachylaella) gronychi subgen. nov., sp. nov., is described and illustrated from the Stara Planina Mountains of Bulgaria. A key to the adults of the known species of the genus Olopachys is provided.